Расчетное и экспериментальное исследование многоцикловой усталости вала паровой турбины мощностью 200 МВт вследствие его крутильных колебаний - Черноусенко, Ольга Юрьевна; Бовсуновский, А. П.; Штефан, Е. В.; Гудов, Р. И. (Национальный технический университет "Харьковский политехнический институт", 2010)
It is spent settlement and an experimental research of cyclic durability rotor’s steels 25Cr1МWА at torsion for steam turbines of power units by capacity 200 MWt, the 275 thousand which have fulfilled in actual practice more 275000 ours. Are received a curve of multi cyclic weariness of samples from a steel 25Cr1МWА at symmetric torsion at temperature 20°С, peak dependence of logarithmic decrement torsion steel fluctuations 25Cr1МWА at a symmetric cycle stress and various average pressure of a cycle. The settlement residual resource of a shaft of turbine K-200-130 TES taking into account total influence of multi cyclic weariness from torsion fluctuations and little cyclic weariness from influence of thermal loadings is defined.
Keywords: повреждаемость валов; усталостное повреждение; разбалансировка; сталь роторная